Ethnobotanical Study of Medicina Ethnobotanical Study of Medicinal Plants Used by the Indigenous Community of Mbaham in Karas District Fakfak Regency West Papua - Ubay, Santi; Fitmawati, Fitmawati (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2024)
Medicinal plants are the main element in the local medicine system in Karas District, Fakfak Regency. This is closely related to the culture and traditional knowledge of the community. This study aims to identify the species of medicinal plants used by Traditional Medicine Practitioners (TMP) An ethnobotanical survey was conducted to collect information from Traditional Medicine Practitioners from January to February 2023. The research method used by interviewing six informants who had information about the use of medicinal plants. The results showed that there were 57 species of medicinal plants from 35 families that had been used to treat 39 types of diseases. The most used plan part by TMP is leaf (19%) Boiling is the most commonly used processing method. Medicinal plants with the highest use value used by TMP are Andrographis paniculata, Annona muricata, Momordica charantia, Terminalia catappa, Jatropha curcas, Spatholobus littoralis, Piper betle, Cymbopogon citratus, Citrus aurantifolia, Curcuma longa, dan Zingiber officinale with a UV value = 1.00. The category of circulatory system is the most treated disease category with an ICF value of 0.8. Medicinal plants with the highest percentage accuracy value are Andrographis paniculata, Annona muricata, Momordica charantia, Terminalia catappa, Jatropha curcas, Spatholobus littoralis, Piper betle, Cymbopogon citratus, Citrus aurantifolia, Curcuma longa, dan Zingiber officinale with FL = 100%. Keywords: Ethnobotany, Karas District, Fakfak, Traditional Medicine Practitioners (TMP), Medicinal Plant.